Impact of the COVID-19 Restrictive Measures on Tuberculosis Detection among Children and Adolescents - R. K. Varlamov; E. S. Prokopiev; E. F. Luginova (Туберкулез и болезни лёгких)
The objective: to assess impact of the COVID-19 restrictive measures on tuberculosis detection among children and adolescents.Subjects and Methods. For the analysis, materials from statistical collections and state statistics forms (Form No. 33) were used. Changes of the main epidemiological tuberculosis rates were assessed for two observation periods: before the pandemic (2017-2019) and during the pandemic (2020-2022). Statistical analysis methods were used.Results. The COVID-19 pandemic and related restrictive measures generally provided no significant impact on the coverage with preventive screening for tuberculosis of population in the Republic of Sakha (Yakutia). At the same time, during the pandemic, a slight reduction of the main epidemiological tuberculosis rates was noted both among adults and children. Despite this decrease, a deterioration in the structure of new tuberculosis patients was revealed, which indicated that the disease was not detected in a timely manner.